Study of synthesis and characterization of bismuth oxyiodide thin film for non- toxic perovskite solar cells - A.H. Azmi; N.A. Abdul Manaf (Penerbit Universiti Kebangsaan Malaysia, 2021)
Perovskite solar cells based on lead halide has demonstrated the fast increase in efficiency and advanced in photovoltaic technology in the last decade. However, perovskite solar cells that contain lead (Pb) has high efficiency but tangible risk to humans, animals, and the environment. Bismuth oxyiodide (BiOI) has been recognized as a suitable candidate of non-toxic material to replace lead without adversely impacting performance in perovskite solar cells. The interest in application of BiOI thin films is because BiOI has narrow band gap, high efficiency light absorption and high photo catalytic activity makes it the perfect contender to replace Pb as new non-toxic material perovskite solar cell. Thin films of BiOI were synthesized and deposited using Successive Ionic Layer Adsorption and Reaction (SILAR) on glass substrates. The same mole ratios of bismuth(III) nitrate pentahydrate (Bi(NO3).5H2O) and potassium iodide (KI) were diluted in deionized water to achieve clear solution. The microscope glass was dipped consecutively in 0.01M of (BiNO3)2.5H2O diluted in deionized water, 0.01M of (KI) diluted deionized water and in 50 ml deionized water. This process has been repeated for 30 times and finally the sample was dripped and dried in air. The sample was annealed at various annealing temperature from 250 °C, 350 °C, 450 °C, and 550 °C for 20 minutes. The optical properties and structural properties of BiOI thin films were characterized using X-ray powder diffraction (XRD), Ultraviolet-visible (UV-Vis) measurement and Field Emission Scanning Electron Microscope (FESEM). The Surface Profilometer (SP) was used to measure the thin films thickness. The structure of the films changed with the annealling temperature. The color of the film changes to the orange-yellow and become more yellowish with increasing annealing temperature. The morphology of FESEM images demonstrated that the BiOI thin films have flakes morphology structure with the size around 1μm. The deposited film thickness ranged between 3.479 μm and 8.082 μm. This study provided significant output and a pathway for non-toxic BiOI thin film for perovskite solar cells.